2014
DOI: 10.1186/1746-1596-9-103
|View full text |Cite
|
Sign up to set email alerts
|

Histological comparison between preoperative and surgical specimens of non-small cell lung cancer for distinguishing between "squamous" and "non-squamous" cell carcinoma

Abstract: BackgroundNon-small cell lung cancers (NSCLCs) are frequently heterogeneous and in approximately 70% of cases, NSCLCs are diagnosed and staged by small biopsies or cytology rather than by examination of surgically resected specimens. Thus, in most patients, the diagnosis is established based on examination of preoperative specimens alone. Recently, classification of NSCLC into pathologic subtypes has been shown to be important for selecting the appropriate systemic therapy, from both the point of view of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Yamagishi et al showed that H + E cores without stains had 94% accuracy for SCC and 79% accuracy for ADC with respect to the final resection diagnosis. In cases where immunostains were added, there was 97% and 91% accuracy for SCC and ADC, respectively . How does this impact our results is difficult to gauge.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Yamagishi et al showed that H + E cores without stains had 94% accuracy for SCC and 79% accuracy for ADC with respect to the final resection diagnosis. In cases where immunostains were added, there was 97% and 91% accuracy for SCC and ADC, respectively . How does this impact our results is difficult to gauge.…”
Section: Discussionmentioning
confidence: 91%
“…Pairwise kappa scores ranged from −0.16 to 0.47. The raters differed ( χ (12) = 104, p < 0.001) in the frequency with which they used intermediate categories (Table ). For example, rater 1 (0%) never used intermediate categories, whereas rater 2 (76%) frequently used the intermediate categories.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 However, accurately subtyping lung cancers histologically and molecularly before treatment is not always achievable primarily due to limited availability of tissue samples. 13 On the other hand, liquid biomarkers such as serum carcinoembryonic antigen (CEA), cytokeratin-19 fragments (CYFR-211) and neuron-specific enolase (NSE) may assist in differentiating the diagnosis, but their specificity and practical values remain to be further evaluated. 14 Characteristic protein profiles determined by proteomic approaches have been increasingly investigated as biomarkers of diagnosis, prognosis and responses to treatment in cancer patients.…”
Section: Introductionmentioning
confidence: 99%